Immunohistochemical staining of leptin is associated with grade, stage, lymph node involvement, recurrence, and hormone receptor phenotypes in breast cancer - Mohamad Nidal Khabaz; Amer Abdelrahman; Nadeem Butt; Lila Damnhory; Mohamed Elshal; Alia M. Aldahlawi; Swsan Ashoor; Basim Al-Maghrabi; Pauline Dobson; Barry Brown; Kaltoom Al-Sakkaf; Mohmmad Al-Qahtani; et al. (BMC, 2017)
Abstract Background Obesity is part of the established risk factors for breast cancer (BC) in postmenopausal females. Circulating leptin increases in parallel with the increase of body weight and fat reservoir. Methods This research investigated the link between leptin phenotype and the clinicopathological factors in BC. A large set of breast cancer cases (449), and 27 non-cancerous tissue samples of breast were employed for leptin expression recognition using immunohistochemistry staining. Results Cytoplasmic immunohistochemical staining of leptin was recognized in 376 (83.7%) and 25 (92.6%) of BC and control cases respectively. Leptin immunostaining were significantly associated with age, histotypes, grade, stage, lymph node involvement, tumor recurrence, hormone receptor phenotypes, ER and HER2 expressions, and p-values were (P = 0.0233), (P = 0.0001), (P = 0.050), (P = 0.0291), (P = 0.0300), (P = 0.0023), (P = 0.0021), (P = 0.0279) respectively. Reasonable proportion of cases with low staining score was more prevalent in all subgroups of clinicopathological parameters except ER- PR+ HER2- hormone receptor phenotype and mucinous carcinoma which showed high level of leptin immunoreactivity. Tumor recurrence is less prevailing in high score leptin immunostaining cases. Furthermore, Log Rank (Mantel-Cox) test findings revealed considerably different survival distributions were observed for the different categories of leptin immunostaining scores (P = 0.032). Negative leptin immunostaining is related to poor survival. Conclusions Our preliminary findings support leptin clinical value in confirming BC diagnosis as well as prognosis. These results suggest that leptin molecule is an important biomarker that could identify type, grade, stage, lymph node involvement, relapse and prognosis in breast cancer.